Morphology, Anatomy and Chemical Composition of Salvia fruticosa Mill in Al-Marj (Libya) - Ahmed , Wafa (Scientific Journal of University of Benghazi, 2023)
Macro, micromorphological and chemical characteristics of Salvia fruticosa Mill, wild growing in Libya were studied. The aim of the present study is to provide new properties for the identification and description of this species. The features of leaf morphology, verticillaster number, bract, calyx, corolla, stamens, trichomes, collenchyma’s rows, vascular bundle and mesophyll structure are important characters to distinguish this species. In the study, we observe morphologically different types of glandular trichomes. The results of leaf architecture studies can provide a more accurate basis for the identification of this species. The essential oil contained cineol (43.93%), β-pinene (11,43%), α-pinene (9.53%), β-myrcene (9.08%), caryophyllene (8.75%), camphor (5.12%) and α-terpineol (4.15%).